2022
DOI: 10.2106/jbjs.21.01142
|View full text |Cite
|
Sign up to set email alerts
|

The Rotator Cable Does Not Stress Shield the Crescent Area During Shoulder Abduction

Abstract: Background:It is accepted by the orthopaedic community that the rotator cable (RCa) acts as a suspension bridge that stress shields the crescent area (CA). The goal of this study was to determine if the RCa does stress shield the CA during shoulder abduction.Methods:The principal strain magnitude and direction in the RCa and CA and shoulder abduction force were measured in 20 cadaveric specimens. Ten specimens underwent a release of the anterior cable insertion followed by a posterior release. In the other 10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Previous research has demonstrated the role of the crescent region in transmitting muscle-generated loads during shoulder abduction 9 , consistent with our findings. We observed significantly higher strains in the anterior third of the rotator cable compared with the middle and posterior thirds, with no significant strain difference between the anterior third and the crescent region during loading of the whole SSP muscle.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Previous research has demonstrated the role of the crescent region in transmitting muscle-generated loads during shoulder abduction 9 , consistent with our findings. We observed significantly higher strains in the anterior third of the rotator cable compared with the middle and posterior thirds, with no significant strain difference between the anterior third and the crescent region during loading of the whole SSP muscle.…”
Section: Discussionsupporting
confidence: 93%
“…Cadaveric studies have investigated the strain distribution in the bursal (superficial) surfaces of the rotator cable and crescent 2,9,10 . Mesiha et al demonstrated increased strains in preserved superficial SSP tendon regions when the anterior insertion of the rotator cable was torn, emphasizing the role of the anterior insertion as the primary load-bearing structure 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 ). 30 , 39 The modeling software was used to quantify the length and width of the tendon footprints and the intact and torn footprint areas. The caliper measurements of length and width were compared to computer-generated values to validate the 3D modeling.…”
Section: Methodsmentioning
confidence: 99%